Musicdrops@work: Impact of Shared Listening to Short Live Music Interventions on Sense of Belonging and Subjective Wellbeing at Work - Güsewell, Angelika; Gay-Balmaz, Sarah; Imseng, Catherine (Frontiers in Psychology, 2022)
Assuming live music can foster belonging in the workplace, this study linked companies in the secondary and tertiary sectors with the world of music performance. Specifically, students from a Swiss music university offered live mini-concerts (10 minutes of classical music) on the premises of three companies over a period of three months. To analyse the impact of these brief musical interventions on the sense of belonging of staff in these companies, a mixed methods approach was adopted using a standardized questionnaire (Barcelona Music Reward Questionnaire, Saliba et al., 2016), a short online questionnaire on the appreciation of the music and the emotional state induced, and focus groups interviews at the end of the experiment. The short concerts were much appreciated. On the individual level, they led to a greater sense of pleasure and were perceived as a break, a possibility to connect to one’s emotions and above all, as a “moment for oneself”. On the group level, the short concerts allowed the members of teams to meet, prompted conversations and new ways of sharing, created links, and offered opportunities to get to know work colleagues differently and to discover them on a more personal level.